2016
DOI: 10.1080/10962247.2016.1149526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different ratios of pig manure to fungus residue on physicochemical parameters during composting

Abstract: Co-composting of pig manure and edible fungi residue with appropriate proportion can effectively reduce the risk of environmental pollution caused by agricultural wastes, as well as achieve a safer and high-quality organic fertilizer, which can be used to improve physical and chemical properties of the soil, increase crop yields, and promote agricultural sustainable development. Therefore, technique of co-composting of pig manure and edible fungi residue has a wide prospect of application in practical producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Generally, during the degradation of organic matter, carbohydrates are classified into two groups and used: (i) bacterial components for 30-40%, and (ii) microbial breakdown and evaporation in the form of CO 2 for 60-70% (Hellmann et al 1997). Thus, the amount of carbon shows a declining trend (Zhou et al 2016). However, our results are the opposite of what would be expected over time.…”
Section: Methodsmentioning
confidence: 52%
“…Generally, during the degradation of organic matter, carbohydrates are classified into two groups and used: (i) bacterial components for 30-40%, and (ii) microbial breakdown and evaporation in the form of CO 2 for 60-70% (Hellmann et al 1997). Thus, the amount of carbon shows a declining trend (Zhou et al 2016). However, our results are the opposite of what would be expected over time.…”
Section: Methodsmentioning
confidence: 52%
“…Each treatment combination consisted of approximately 2100 kg pig manure, 500 kg fungus residues, and 600 kg rice bran. A previous study had concluded that this is the optimal mixing ratio that is suitable for efficient and quality composting (Zhou et al, 2016). Windrows were not duplicated because of the limitation of both the heavy work and a project budget and because the variability between the respective windrows was similar to that of duplicate samples of a single windrow (Tirado and Michel, 2010).…”
Section: Composting Setup and Designmentioning
confidence: 99%
“…However, there are large previous studies of successful pig manure composting mainly using sawdusts, rice brans, and cornstalks as carbon source to mix with pig manure, and rare literature reportes of the co-composting with pig manure and fungus residue, except estimated ratios of pig manure to fungi residue in composting with pig manure and fungus residue (Zhou et al, 2016). In recent years, co-composting has been used commonly in China.…”
Section: Introductionmentioning
confidence: 99%
“…Heterotrophic fungi belonging to the genera Aspergillus, Penicillium, Mucor, Rhizopus, Alternaria, Beauveria, Paeclomyces, and Candida have been found to be dung-loving and to tolerate oilcontaminated environments (Dawodi et al 2015;Ughamba et al 2019). Findings from this work corroborate the report of several workers who found Candida sp., C. tropicalis, Rhizopus sp., Mucor sp., Aspergillus spp., A. niger to be strongly associated with cow and pig dung (Obire et al 2008;Zhou et al 2016;Samuel et al 2017) A wide variety of members of fungal divisions are found on dung; the Mucoromyceta (Zygomyceta) usually appear first, followed by Ascomycota and then the Basidiomycota. Presentations in Table 1 indicated that three fungal divisions colonized the test dung specimens; these were saprobes of the division Ascomycota, Mucoromyceta and Basidiomycota.…”
Section: Discussionmentioning
confidence: 99%
“…Dung is rich in carbohydrates, protein, some water-soluble vitamins and mineral ions (Gupta et al 2016). Being rich in carbon, nitrogen and moisture, pig dung is a good substrate that supports the growth of bacteria and various fungi, that participate in nutrient recycling in the ecosystem (Abdullah 1982;Bills et al 2013;Zhou et al 2016;Samuel et al 2017).…”
Section: Introductionmentioning
confidence: 99%